2022
DOI: 10.3390/ijerph19116898
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Relationships among the Natural Environment, Health, and Sociodemographic Characteristics across US Counties

Abstract: Background: The aim of this study was to explore the nonlinear relationships between natural amenities and health at the intersection of sociodemographic characteristics among primary care patients with chronic conditions. Methods: We used survey data from 3409 adults across 119 US counties. PROMIS-29 mental and physical health summary scores were the primary outcomes. The natural environment (measured using the County USDA Natural Amenities Scale (NAS)) was the primary predictor. Piecewise spline regression m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Studies on health and climate and the natural environment have shown that health and the natural environment are inextricably linked [ 88 , 89 ]. As society develops, the natural environment is constantly changing the way humans produce and live, balancing the material and energy exchange between humans and the environment [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on health and climate and the natural environment have shown that health and the natural environment are inextricably linked [ 88 , 89 ]. As society develops, the natural environment is constantly changing the way humans produce and live, balancing the material and energy exchange between humans and the environment [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation is that greenness can reduce air pollution levels and thus contribute to people’s health condition [ 25 ]. Another explanation can be that greenness exposure may promote opportunities for more physical activity engagement [ 68 ]. However, greenness exposure may not have a significant impact on dyslipidemia across a diversified greenness area, vegetation type, and exposure level [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that most natural environments have restorative effects on humans (Bonnell & Littenberg, 2022; Egner et al, 2020). However, the mechanisms of how nature‐based tourism activities impact tourists' perceived health benefits are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that most natural environments have restorative effects on humans (Bonnell & Littenberg, 2022;Egner et al, 2020).…”
Section: Introductionmentioning
confidence: 99%